I Was a Percussionist in a Fanfare Band - Taekema, Riek (Homœopathic Links, 2018)
This patient is suffering from headaches early in the morning, it forces him to get up and he can't enjoy being retired and sleep his fill. He is very negative about people and the world. He likes to talk to people but in the meantime keeps them at distance. This case helps us understand the mind of a Nitricum acidum patient.
Keywords: Loquacity; Negativity; Proudness; Hatred; Revenge; Disappointment; Love for music; Drumming; Nitricum acidum; Sulphur